3 Mortality on orthotopic liver transplantation waiting list at national liver transplant unit ireland. (5th April 2017) - Christopher, BT; Ismail, MS; Kiat, C; Tatro, E; McGarry, Y; MacNicholas, R; McCormick, PA; Houlihan, D
Abstract : Background: Orthotopic liver transplantation is indicated in patients with end-stage liver disease, hepatocellular carcinoma (HCC) within transplant criteria and acute fulminant hepatic failure. Progression to end stage liver failure with high mortality is inevitable without transplantation. Aim: Our aim is to analyse mortality aspects on our OLT waiting list. This retrospective study included patients' cohort over 3 years from January 2014 to December 2016. During this time period, there were 163 patients transplanted. Method: Data was collected from database and patients' medical records. Results: There were 21 deaths (6 females, 15 males) with 8 patients delisted and 4 suspended. The median patients' age was 50. Nine patients (43%) died on waiting list. Of these, three were listed as super-urgent for fulminant hepatic failure (2 acetaminophen overdose1 autoimmune hepatitis). Median duration on waiting list to death was 3.6 months. There was one patient followed up regularly with 16 months duration on waiting list. The remainder waiting duration was single figured in months. The average MELD score at time of listing was 19(7-53). Causes of death include multi-organ failure (n=5), coroner's case (n=4), end stage liver failure progression (n=4), bleeding oesophageal varices and sepsis (n=1), metastatic cancer recurrence (n=1) and not documented in 6 others. Aetiology of liver disease subgroups are shown in Table 1 (attached). There were 10 patients each in blood group O and A and 1 in blood group B. Conclusions: Limited organ availability and increasing demand for organ transplantation has extended transplant waiting times, thus increased morbidity and mortality for potential recipients.